2013
DOI: 10.4067/s0718-34292013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of droplets produced by use of adjuvants

Abstract: Adjuvants are products added to spray solution in order to attend the pesticides application. However, their effects in the technical parameters of the spray are not yet fully understood. The objective was to evaluate the effects of addition of five adjuvants (A, B, C, D and E) and five dilutions (D1 = 30; D2 = 40; D3 = 50; D4 = 60 e D5 = 70 mL per 100 liters of water), and a control (distilled water) in the technical parameters of the spraying (Dv 0.1 ; Dv 0.5 ; Dv 0.9 and Span index). The analysis of the dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…When comparing the VMD of the impacted droplets on hydrosensitive paper and the droplets in transit, an overestimation of the VMD of the impacted droplets was observed, since, as Nascimento (2020) noted, the characterization of the spectra of droplets in transit or VMD was much lower than that observed in hydrosensitive papers, thus, the device read a droplet with an overestimated VMD. The relative amplitude, on the other hand, shows the sprinkler quality of the spectrum, so that the lower the relative amplitude value, the more homogeneous the droplets are (Sasaki et al 2013). All tips evaluated in the present study showed similar droplet homogeneity in the three thirds of the plants.…”
Section: Discussionmentioning
confidence: 50%
“…When comparing the VMD of the impacted droplets on hydrosensitive paper and the droplets in transit, an overestimation of the VMD of the impacted droplets was observed, since, as Nascimento (2020) noted, the characterization of the spectra of droplets in transit or VMD was much lower than that observed in hydrosensitive papers, thus, the device read a droplet with an overestimated VMD. The relative amplitude, on the other hand, shows the sprinkler quality of the spectrum, so that the lower the relative amplitude value, the more homogeneous the droplets are (Sasaki et al 2013). All tips evaluated in the present study showed similar droplet homogeneity in the three thirds of the plants.…”
Section: Discussionmentioning
confidence: 50%
“…Droplets with initial diameters less than 100 μm are generally considered highly driftable. [37] In this sense, the results of both models agreed that 100 μm droplets were the most susceptible to wind-induced spray drift, depositing at the greatest distances from the nozzle. On the other hand, droplets with initial sizes of 50 μm show a significant tendency to evaporate completely before reaching the ground (i.e., evaporation drift).…”
Section: Parametermentioning
confidence: 55%
“…(Aliverdi and Karami 2020). This is also true for other groups (mode of actions) of herbicides against easy-to-wet species (Knoche 1994;Huang et al 2000;Shaw et al 2000;Sasaki et al 2013;Creech et al 2015;Meyer et al 2016). Due to a low level of energy existing in smaller spray droplets, they can easily be deposited on the leaf surface, leading to greater efficacy of the herbicide (Penner 2000).…”
Section: Resultsmentioning
confidence: 97%